1976
DOI: 10.1575/1912/1792
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter sinking to the deep-sea floor at 2000 M in the Tongue of the Ocean, Bahamas, with a description of a new sedimentation trap

Abstract: Comparison of the sedimentation trap estimates of organic carbon input to the sea floor in this area with benthic energy requirements indicates that rapidly sinking small particulate matter could supply approximately 14% of the metabolic requirements of the benthos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

1980
1980
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 19 publications
2
32
0
2
Order By: Relevance
“…Fowler & Small found higher rates of sinking for euphausiids than Smayda (1969). Wiebe et al (1976) obtained faecal pellets with sediment traps. The faeces were counted under a microscope, measured and subsequently frozen until the measurement of the rate of sinking.…”
Section: Discussionmentioning
confidence: 99%
“…Fowler & Small found higher rates of sinking for euphausiids than Smayda (1969). Wiebe et al (1976) obtained faecal pellets with sediment traps. The faeces were counted under a microscope, measured and subsequently frozen until the measurement of the rate of sinking.…”
Section: Discussionmentioning
confidence: 99%
“…However, larger parcels of organic matter, including coastal and terrestrial macrophytes (e.g. Menzies et al 1967;Schoener and Rowe 1970;Wiebe et al, 1976;Suchanek et al 1985;Wolff 1979) and pelagic animals (e.g. Jannasch 1978;Cacchione et al 1978), have been observed on the deep sea floor and are also passively transported through the water column.…”
Section: Discussionmentioning
confidence: 99%
“…These were largely derived from research focused on the ecology of deep-sea fauna (e.g., Wolff, 1979) and carbon sources to marine food webs (Baeta et al, 2009), and also included research motivated by the study of organic matter fluxes to the deep sea (e.g., Wiebe et al, 1976), surveys of marine debris (Wei et al, 2012), assessments of kelp contributions to deep-sea sediments (e.g., Harrold et al, 1998), and assessments of the sources of sediment organic matter (e.g., Boysen-Jensen, 1914;Boschker et al, 2000), among other research topics. Taken in concert, however, these reports produce strong and compelling evidence that seagrass meadows contribute to sedimentary carbon stocks in bare sediments extending from shallow littoral areas to the hadal regions of the ocean.…”
Section: Contribution Of Exported Seagrass Carbon To Carbon Sequestramentioning
confidence: 99%